Amplifying Digital Literacy Through Non-Profit Organizational Communication in a Sensemaking Perspective - Wardah Fazriyati; Achmad Jamil (Eduvest - Journal of Universal Studies, 2025)
Digital transformation and acceleration during the pandemic and post-COVID-19 pandemic provide a high adaptation challenge for non-profit organizations in increasing their capacity to adopt and utilize digital technology optimally in order to achieve their mission. Amplification of digital literacy can answer the challenge of improving individual technical skills in using digital technology, by involving a collective process in organizations to build understanding in support of common goals. This study aims to find out how organizational communication in the process of amplifying digital literacy in non-profit organizations in understanding, responding to and overcoming digital literacy challenges to achieve their social goals, using the perspective of organizational communication through Karl Edward Weick's sensemaking theory. Karl E. Weick's sensemaking perspective highlights the process that occurs continuously and is influenced by communication with others in understanding the world around us when faced with a new or confusing situation, which encourages the active search for information, trying to understand it, and then deciding how to act based on a common understanding. This case study method analyzes data from interviews, document observations, and literature review, conceptualization and validation of data by triangulation of sources. The study of digital literacy amplification refers to strategic and sustainable efforts to expand reach, increase impact, and ensure the sustainability of programs that aim to improve the ability of individuals and organizations to use digital technology effectively, critically, and responsibly.